Insulator–metal transition in VO2 film on sapphire studied by broadband dielectric spectroscopy - Arsenii A. Gavdush; Vladislav A. Zhelnov; Kirill B. Dolganov; Alexander A. Bogutskii; Sergey V. Garnov; Maria G. Burdanova; Dmitry S. Ponomarev; Qiwu Shi; Kirill I. Zaytsev; Gennadii A. Komandin (Scientific Reports)
Abstract Vanadium dioxide ( $$\hbox {VO}_2$$ ) is a favorable material platform of modern optoelectronics, since it manifests the reversible temperature-induced insulator-metal transition (IMT) with an abrupt and rapid changes in the conductivity and optical properties. It makes possible applications of such a phase-change material in the ultra-fast optoelectronics and terahertz (THz) technology. Despite the considerable interest to this material, data on its broadband electrodynamic response in different states are still missing in the literature. This hampers the design and implementation of the $$\hbox {VO}_2$$ -based devices. In this paper, we combine the Fourier-transform infrared (FTIR) spectroscopy, THz pulsed spectroscopy (TPS), and four-contact probe method to study the $$\hbox {VO}_2$$ films prepared by magnetron sputtering on a c-cut sapphire substrate. Considering different temperatures of a substrate and pressures of atmosphere, we reconstruct complex dielectric permittivity of $$\hbox {VO}_2$$ film in the frequency range of 0.2–150 THz, along with its static conductivity. The dielectric response is modeled using Lorentz and Drude kernels, which make possible splitting contributions from vibrational modes and free charge carriers to the total dynamic conductivity. By studying $$\hbox {VO}_2$$ at different substrate temperatures and atmosphere pressures, we show that IMT appears to be pressure-dependent, which we attribute to the different thermostatic conditions of a sample. Finally, we estimate somewhat optimal thickness and temperature of the $$\hbox {VO}_2$$ film in metallic phase for the THz optoelectronic applications. Our finding should be useful for further developments of the $$\hbox {VO}_2$$ -based devices and technologies.